Features of the emotional portrait of teen-age girls in the context of their color-sensory attitude to modern communication technologies and state of anxiety. - I. Vysochyna; I. Avramenko; V. Kramarchuk; T. Yashkina (Medičnì Perspektivi, 2020)
This work is a continuation of previous studies on the relationship of high anxiety and the use of modern electronic communication tools. The purpose of this study was to determine the characteristics of the emotional portrait of adolescent girls in the – context of their color-sensory attitude to modern communication technologies and state of anxiety. The study involved 136 girls aged 17 years (at the time of the survey). All respondents were evaluated according to standardized valid psychological methods (WAM - well-being, activity and mood), color relationship test (TCR), the method of "Multidimensional assessment of child anxiety" (MACAQ), the personal Taylor anxiety manifestation scale in the modification of Norakidze) and contained an author's questionnaire regarding the time spent in a sitting position; time spent in front of the screen of a mobile phone, tablet, laptop, PC; problems in relationships with parents. The study was conducted in accordance with the bioethical principles and provisions of the Helsinki Declaration and Good Clinical Practice (GCP). In the course of the work, it was proved that the time spent near the screens of electronic devices (phone, tablet, laptop, PC) for more than 6 hours a day is a significant factor, which is a predictive of emotional disorders in adolescent girls due to disruption of compensation mechanisms and the formation of a high level of personal anxiety, the appearance of achromatic sensory-color associations in interpersonal interactions, exacerbation of family conflicts with parents, which together indicates maladaptation and requires disruption work corrective programs.